Symposium Honoring Justice Ruth Bader Ginsburg - L'Heureux-Dubé, Claire (Columbia Journal of Gender and Law, 2013)
I must, at the outset, disclose my “multiple partiality”.. . I have been an unconditional admirer of Justice Ginsburg and her jurisprudence since she was appointed to the Supreme Court of the United States. Since older, afortiori our respective backgrounds as early career women in law offer a lot of similarity, and I was myself the second woman to sit on the Supreme Court of Canada. Further disclosure: Justice Ginsburg and I share a passion: opera and a fate (or is it a curse?)-dissents. Her vision of equality and, in particular, gender justice has inspired many. I am one of those. Gender justice is part and parcel of the much larger issue: that of equality. A discussion about equality must start with the question: why is equality so important both for the law and the people? The answer for me is simple: inequality is injustice, it is the negation of human dignity. My own definition of gender equality is the “extraordinary” notion that women are human beings entitled to the same respect, consideration and opportunities as other members of society. That definition applies, mutalis mutandis, to all those subject to discrimination by reason of their ethnicity, sexual orientation, religion, social status, etc. Justice Brennan said it this way: “Human relations are extremely complex” and “the law is there to serve . .. the realization of man’s ends, the ultimate and the ‘immediate . . . the realization of human dignity through full opportunity and the eradication of bias.” Full opportunity for women is a theme that resonates more than once in Justice Ginsburg’s jurisprudence.